Improving the Performance of Goods and Services Procurement through the Implementation of the SPSE INAPROC System at the Regional Secretariat of Belitung Regency - Eka Indah Wahyuni; Tulas Novalima (INFOKUM, 2025)
This research is intended to provide an overview of how improving the performance of goods and services procurement can be achieved through the utilization of the SPSE INAPROC System at the Regional Secretariat of Belitung Regency. The utilization of this electronic system is considered a strategic step to implement a more open, efficient, and accountable procurement process. The research used a descriptive qualitative method by collecting data through interviews, observations, and document reviews related to procurement activities. The findings show that SPSE INAPROC helps speed up the administrative flow, evaluate the quality of documentation, and reduce the potential for manual errors that previously often appeared. In addition, the system expanded supplier involvement and increased the level of public disclosure of procurement-related information. However, the study also found that there were constraints including limited human resource capacity, technical understanding of suppliers, and network and infrastructure factors. Overall, the implementation of INAPROC's SPSE has made an important contribution to improving procurement performance, although various supporting aspects still need to be strengthened.